Small bowel polyp resection using device-assisted enteroscopy in Peutz-Jeghers Syndrome: Results of a specialised tertiary care centre. Issue 2 (March 2020) - Perrod, G; Samaha, E; Perez-Cuadrado-Robles, E; Berger, A; Benosman, H; Khater, S; Vienne, A; Cuenod, C-A; Zaanan, A; Laurent-Puig, P; Rahmi, G; Cellier, C
Introduction: Enteroscopy resection of small bowel polyps in Peutz-Jeghers syndrome has only been described in small case series. Herein, we aimed to assess the efficacy of enteroscopy resection of small bowel polyps within a specialised tertiary care centre and the impact on intraoperative enteroscopy. Methods: This was an observational single-centre study. All adult Peutz-Jeghers syndrome patients followed in the Predisposition Digestive Ile-de-France network who underwent an endoscopic resection of at least one small bowel polyp ≥ 1 cm by enteroscopy between 2002–2015 were included. Small bowel polyps were detected under a dedicated screening programme by previous capsule endoscopy and/or magnetic resonance enterography, performed every 2–3 years. Complete treatment was defined as the absence of polyps ≥ 1 cm after conventional endoscopic resection. Intraoperative enteroscopy or surgical resection were indicated in incomplete treatments. The overall complete treatment rate including conventional enteroscopy and intraoperative enteroscopy was also considered. Results: Endoscopic resection of 216 small bowel polyps (median: 8.6 per patient, size: 6–60 mm) was performed by 50 enteroscopies in 25 patients (mean age: 36 years, range: 18–71, 56% male) with small bowel polyp ≥ 1 cm. Twenty-three patients (92%) underwent 42 screening capsule endoscopies and 14 (57%) had 23 magnetic resonance enterographies during a median follow-up of 60 months. Complete treatment was achieved in 76%. Intraoperative enteroscopy and surgical resection were performed in four (16%) and two (8%) patients. Intraoperative enteroscopy improved by 16% the complete treatment rate and the overall rate was 92%. The complication rate was 6%. Conclusion: This long-term study confirmed the efficacy and safety of endoscopic resection of small bowel polyps in Peutz-Jeghers syndrome. Intraoperative enteroscopy can be a complementary approach in selected cases.